S-Layer protein from Lysinibacillus sphaericus JG-A12 as matrix for AuIII sorption and Au-nanoparticle formation. Issue 1 (2010) - Jankowski, Ulrike; Merroun, Mohamed L.; Selenska-Pobell, Sonja; Fahmy, Karim
Abstract : The strain Lysinibacillus sphaericus JG-A12, isolated from the uranium mining site at Haberland, Saxony (Germany) selectively and reversibly accumulates radionuclides and toxic metals. Metal binding occurs to its surface layer (S-layer) surrounding the cells. Here, we have studied by Fourier-transform infrared (FTIR) spectroscopy the protein structure and stability as a function of Au III binding and the subsequent reductively induced formation of Au-nanoclusters. Similar to previously studied complexes with Pd II, Au-treated S-layers become resistant to acid denaturation evidenced by little response of their amide I absorption frequency. However, the strong effect of Pd II exerted on the side chain carboxylate IR absorption intensity is not observed with gold. Particularly after reduction, the carboxyl absorption responds little to acidification and a fraction appears to be protonated already at neutral pH. We ascribe this to a hydrophobic environment of the carboxyl groups after formation of Au-nanoclusters. EXAFS spectra agree with the metallic Au–Au distance but the reduced coordination number indicates that the Au-nanoclusters do not exceed ~2 nm. Thus, the S-layer of L. sphaericus JG-A12 provides a biotemplate for efficient Au-nanocluster formation in an acid-resistant matrix and independently of cysteins.